Contribuciones a la generalización del problema de compensación por grupos de Helmert-Pranis Pranievich - Popescu, Ioan (Revista Matemática Complutense, 1988)
. The papa presents in a generalized form the problem of the geodetic network adjustment by the Helmert-Pranis Pranievich &ouP~ method (groups with junction points included or not). The adjustment problem, as well as the cobactor matrix derivation for the partialindependent and linkage unknowns, was completely formulated by transformed weight matrix deftnition and usage. A complete sequence of the computing stages for